Growth and yield response of local soybean in the giving of various organic fertilizer. Issue 1 (November 2021) - Rahayu, M; Purwanto, E; Setyawati, A; Sakya, A T; Samanhudi,; Yunus, A; Purnomo, D; Handoyo, G C; Arniputri, R B; Na'imah, S
Abstract: Soybean is the basic material for any kind of industry, such as tofu and tempeh industries. Soybean cultivation will be better if use a sustainable agricultural system, such as using organic fertilizers. This research purpose was to find out the effect of organic fertilizer on the growth and yield of local soybean. The research used a complete randomized design with one factor which was a variety of organic fertilizers with 6 treatments. Various fertilizers used in this research consist of inorganic fertilizer, liquid organic, compost, cow manure, rabbit urine, chicken manure, and goat manure. Each test unit consists of 4 pots (plants) and each was repeated 4 times. The results showed that the provision of compost and goat manure increased the growth of local soybean plants, include plant height and the number of leaves at 42 DAP and leaf area at 28 DAP. The application of various organic fertilizers (liquid fertilizer, compost, cow manure, goat manure, and rabbit urine) is unable to increase the yield and yield components of local soybeans.